2015
DOI: 10.1155/2015/270876
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial for the Effectiveness of Progressive Muscle Relaxation and Guided Imagery as Anxiety Reducing Interventions in Breast and Prostate Cancer Patients Undergoing Chemotherapy

Abstract: Objective. To test the effectiveness of guided imagery (GI) and progressive muscle relaxation (PMR) as stress reducing interventions in patients with prostate and breast cancer who undergo chemotherapy. Methods. Patients were randomly assigned to either the control group or the intervention group (PMR and GI). Patients were observed for a total duration of 3 weeks and assessed with the SAS and BECK-II questionnaires for anxiety and depression, respectively, in addiotion to two biological markers (saliva cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
18

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 37 publications
5
52
1
18
Order By: Relevance
“…The present study result agrees with the results of Li et al (2015), [37] Charalambous et al (2015) [38] and El Malky (2015). [39] The first, had studied Progressive Muscle Relaxation Improves Anxiety and Depression of Pulmonary Arterial Hypertension Patients.…”
Section: Discussionsupporting
confidence: 93%
“…The present study result agrees with the results of Li et al (2015), [37] Charalambous et al (2015) [38] and El Malky (2015). [39] The first, had studied Progressive Muscle Relaxation Improves Anxiety and Depression of Pulmonary Arterial Hypertension Patients.…”
Section: Discussionsupporting
confidence: 93%
“…Only 5 studies showed a large ES ranging between −0.80 and −1.43, while 7 studies reported medium ESs ranging between −0.53 and −0.75. Factors which characterised studies with moderate to large ES were recruiting patients with high level of anxiety symptoms, intervention method well‐matched to patients' needs, recruiting patients who were undergoing highly stressful cancer treatments, and specifically targeting anxiety treatments …”
Section: Resultsmentioning
confidence: 99%
“…Patients who self‐reported respiratory distress symptoms (breathlessness, cough, or fatigue) or psychological complaint (such as anxiety) were included in 2 studies . Another 2 studies considered provider‐reported anxiety and depression as well as psychological needs as reliable sources of sample inclusion criteria and delivered progressive muscle relaxation and CBT, respectively (n = 2, ES: −0.40) (Table ) . However, these 4 studies did not use a standard screening tool to determine anxiety symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pós Pré Pós Moda 2 0 0 0 Média (dp) 22,5 (18,9) 20,1 (19,6) 21,1 (19,8) , 2015) ou três semanas (CHARALAMBOUS et al, 2015), obtendo resultados positivos a respeito das intervenções não-farmacológicas testadas. Outro fator a ser levado em consideração é a dinâmica do serviço de atendimento dos pacientes, local do estudo.…”
Section: Gc Ge Préunclassified